Segmented interlocking nail: An in vivo evaluation of a novel humeral osteotomy fixation device in a caprine model - Stephens, T. J.; Montgomery, R. D.; Edmondson, M. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2012)
Objectives: To describe a novel humeral fixation device, the insertion technique, healing of humeral osteotomies, and clinical outcomes in a caprine model over a six month period.Methods: Fourteen mature female Boer/Nubian cross goats with a mean body weight of 50.7 kg were implanted with a proprietary segmented interlocking nail (SILN) in both humeri. Each goat had one humerus randomly selected for mid-diaphyseal osteotomy.Results: Immediately after surgery all but one goat was able to stand, although none of the goats were weight bearing on the osteotomy limb. During the six month study, clinical lameness was always associated with the osteotomy limb. One month after surgery, lameness for twelve of the goats was grade 2/5 or better. At three months, 11 of the 14 did not exhibit any signs of lameness. On radio-graphic images, notable malalignment of the osteotomy was observed, although all osteotomies went to bone union.Clinical significance: The results of this study suggest that despite misalignment, the SILN maintained adequate osteotomy fixation to achieve bone union in the research model studied, with reduced morbidity and early return to function with bilateral implantation. The SILN used in this study allowed intramedullary fixation of humeral diaphyseal osteotomies with a limited and safe surgical approach.
Keywords: Segmented; humerus; interlocking nail; osteotomy